2013
DOI: 10.1016/j.febslet.2013.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty2 but not Sprouty4 is a potent inhibitor of cell proliferation and migration of osteosarcoma cells

Abstract: a b s t r a c tAs negative regulators of receptor tyrosine kinase-mediated signalling, Sprouty proteins fulfil important roles during carcinogenesis. In this report, we demonstrate that Sprouty2 protein expression inhibits cell proliferation and migration in osteosarcoma-derived cells. Although earlier reports describe a tumour-promoting function, these results indicate that Sprouty proteins also have the potential to function as tumour suppressors in sarcoma. In contrast to Sprouty2, Sprouty4 expression faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 46 publications
3
40
0
Order By: Relevance
“…Spry2 has been found to inhibit cellular functions central to malignant behavior of cancer cells, including cell proliferation, differentiation, migration and invasion, in leiomyosarcoma, osteosarcoma, hepatocellular carcinoma, neuroblastoma, B‐cell lymphoma, non‐small cell lung cancer (NSCLC), cervical cancer and breast cancer cells. Lo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Spry2 has been found to inhibit cellular functions central to malignant behavior of cancer cells, including cell proliferation, differentiation, migration and invasion, in leiomyosarcoma, osteosarcoma, hepatocellular carcinoma, neuroblastoma, B‐cell lymphoma, non‐small cell lung cancer (NSCLC), cervical cancer and breast cancer cells. Lo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Identifying Spry2 as an inducible, negative regulator of HGF/SF-induced activation of ERK and AKT, Lee et al [63] reported in 2004 that Spry2 inhibits proliferation, anchorage-independent growth, migration, and invasion of SK-LMS-1 human leiomyosarcoma cells in vitro . Rathmanner et al reported that Spry2, but not Spry4, potently inhibits proliferation and interfere with migration of human osteosarcoma-derived cells, with the N-terminal sequence variation being implicated in the specific inhibitory effect of Spry2 [169]. Osteosarcoma cell invasion was also shown to be impeded by overexpressed Spry1 as a result of interaction with uPAR [59].…”
Section: Deregulation Of Sprouty In Cancermentioning
confidence: 99%
“…The proliferative effect of Spry 2 knock down may also be attributed to enhanced Erk activity, as Erk is also a potent regulator of MSC proliferation in response to many stimuli [Rodrigues et al, ]. Interestingly, Spry 2 expression has been shown to interfere with Erk activation after stimulation of osteoblasts and to inhibit cell proliferation and migration in osteosarcoma‐derived cells [Yang et al, ; Rathmanner et al, ].…”
Section: Discussionmentioning
confidence: 99%